After the conservation project: conditions and prospects - Wadley, R.L.; Dennis, R.A.; Meijaard, E.; Erman, A.; Valentinus, H. (2000)
This research note provides a brief look at the Danau Sentarum National Park (DSNP), West Kalimanta, Indonesia, and its vicinity after the end of the conservation project. It describes the current threats to the park which largely come in the form of boundary confusion, oil palm plantations, mining, logging, boundary disputes, and fisheries decline. It also considers some bright spots such as NGO activities that have followed the conservation project, positive aspects of local logging, and increased community autonomy. Finally the paper discusses prospects for wildlife management in the new era of reform in Indonesia.